THE INDONESIAN GOVERNMENT'S STRATEGY IN TACKLING THE THREAT OF NARCOTICS SMUGGLING IN THE MARITIME BORDER AREA OF RUPAT ISLAND YEAR OF STUDY 2010-2016 - Jamilah, Mariam; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to describe the potential threat of transnational crime in the field of narcotics smuggling faced by the Government of Indonesia in the maritime border area of Rupat Island and to describe the strategy of the Indonesian Government in overcoming the threat of narcotics smuggling in the maritime border area of Rupat Island. In guiding data retrieval and discussion, this study uses a neorealism perspective that focuses on system structure, interacting units, and on system continuity and change with the main theory of decision making. This study used the descriptive qualitative method.The research found that: first, the sea border area of Rupat Island is vulnerable to the threat of narcotics smuggling from abroad. Its position in the waters of the Malacca Strait is a potential place for the smuggling of narcotics; second, in tackling the threat of narcotics smuggling, the Indonesian Government at least put forward a strategy to strengthen the border area by forming the National Border Management Agency (BNPP) and a strategy to strengthen the action to prevent the threat of Narcotics Smuggling by establishing the National Narcotics Agency (BNN).This study concludes that the Indonesian Government's strategy in tackling the threat of narcotics smuggling can conceptually be effective, but at the level of implementation in the maritime border area of Rupat Island, there are not many traces of it in strengthening national insight, strengthening defense and security, strengthening economic infrastructure and strengthening socio-culture. Keyword: Strategy, decision, security, border, narcotic